Scaffolding reflective learning in clinical practice: A comparison of two types of reflective activities. (July 2014) - Embo, M. P. C.; Driessen, E.; Valcke, M.; Van Der Vleuten, C. P. M.
Abstract Background: The development of reflective learning skills is a continuous process that needs scaffolding. It can be described as a continuum, with the focus of reflection differing in granularity from recent, concrete activities to global competency development. Aim: To explore learners' perceptions regarding the effects of two reflective writing activities designed to stimulate reflection at different degrees of granularity during clinical training. Methods: Totally 142 respondents (students and recent graduates) completed a questionnaire. Quantitative and qualitative data were triangulated. Results: Immediate reflection-on-action was perceived to be more valuable than delayed reflection-on-competency-development because it facilitated day-to-day improvement. Delayed reflection was perceived to facilitate overall self-assessment, self-confidence and continuous improvement, but this perception was mainly found among graduates. Detailed reflection immediately after a challenging learning experience and broad reflection on progress appeared to serve different learning goals and consequently require different arrangements regarding feedback and timing. Conclusions: Granularity of focus has consequences for scaffolding reflective learning, with immediate reflection on concrete events and reflection on long-term progress requiring different approaches. Learners appeared to prefer immediate reflection-on-action.